Transmission electron microscopy image based micromagnetic simulations for optimizing nanostructure of FePt-X heat-assisted magnetic recording media. (1st April 2022) - Bolyachkin, A.; Sepehri-Amin, H.; Suzuki, I.; Tajiri, H.; Takahashi, Y.K.; Srinivasan, K.; Ho, H.; Yuan, H.; Seki, T.; Ajan, A.; Hono, K.
Abstract: The areal density of the heat-assisted magnetic recording (HAMR) technology has a potential to reach 4 Tb/in 2 . However, the bimodal grain size distribution and structural defects that are unavoidable in actual FePt-X nanogranular media must be minimized for further reduction of a jitter noise. Here we report transmission electron microscopy (TEM) image based micromagnetic simulations of the FePt-X nanogranular media in order to elucidate the role of structural defects such as [200] misalignment and {111} twins on the magnetic properties. Micromagnetic approximation of experimental out-of-plane hysteresis loops allows to evaluate micromagnetic parameters and volume fractions of the defects in MgO(6 nm)/FePt-BN(1 nm)/FePt-(BN, C, SiO2 )(7 nm) granular thin films. Synchrotron XRD of the films validated that the structural defects can be accurately evaluated by the proposed approach. The developed TEM image based micromagnetic simulations can directly link nanostructure of the FePt-X media with magnetic properties, boosting not only the optimization of the HAMR media but also a design of magnetic nanomaterials in general. Graphical abstract: Image, graphical abstract